Os desafios atuais mais fundos à vida religiosa - Vigil, José María (Revista Eclesiástica Brasileira, 2004)
O artigo de José Maria Vigil, Claretiano, enumera, no momento “Ver”, os mais fundos desafios que a Vida Religiosa (VR) enfrenta em nossa época. A seguir, no momento “Julgar”, chama a atenção para as profundas e céleres mudanças que estão ocorrendo nesta “época-eixo”, tanto na dimensão temporal como na espacial. Num terceiro momento, o do “Agir”, identifica as tarefas que acredita poder deduzir desta situação para a VR. Em particular, sugere: a) recuperar a teologia da VR; b) recuperar a antropologia da vida radical; e c) adequar o capital simbólico da VR. Concluindo, sintetiza suas propostas em duas grandes tarefas: 1) “desabsolutizar o cristocentrismo da VR”, e 2) “reinocentralizar a VR”. Reflexão pertinente quando se pensa na “refundação” da VR! Abstract: The article by José Maria Vigil, a Claretian, lists, in the moment “See”, the gravest challenges faced by the Religious Life (RL) in our times. In the moment “Judge” he calls attention to the deep and fast changes that are taking place in this “axle-age” both in the temporal and in the spatial dimensions. In a third moment – that of “Act” – he identifies the tasks that, in his opinion, should be carried out by the RL in the present situation. In particular, he suggests: a) rescue the theology of the RL; b) rescue the anthropology of the radical life; c) adjust the symbolic capital of the RL. In the conclusion, he synthesizes his proposals into two large tasks, namely: 1) “make the Christ-centrism of the RL less absolute” and 2) “make the RL more Kingdom-centric”. A pertinent idea when one thinks of the “re-founding” of the RL!